Visiting Richard Serra’s “Promenade” sculpture improves postural control and judgment of subjective visual vertical - Kapoula, Zoï; Lang, Alexandre; Lê, Thanh-Thuan; Adenis, Marie-Sarah; Yang, Qing; Lipede, Gabi; Vernet, Marine (Frontiers in Psychology, 2014)
Body sway while maintaining an upright quiet stance reflects an active process of balance based on the integration of visual, vestibular, somatosensory and proprioceptive inputs. Richard Serra’s Promenade sculpture featured in the 2008 Monumenta exhibition at the Grand Palais in Paris, France is herein hypothesised to have stimulated the body’s vertical and longitudinal axes as it showcased 5 monumental rectangular solids pitched at a 1.69° angle. Using computerised dynamic posturography we measured the body sway of 23 visitors when fixating a cross, or when observing the artwork (fixating it or actively exploring it with eye movements) before and after walking around and alongside the sculpture (i.e., before and after a promenade). A first fixation at the sculpture increased medio-lateral stability (in terms of spectral power of body sway). Eye movement exploration in the depth of the sculpture increased antero-posterior stability (in terms of spectral power and cancelling time of body sway) at the expense of medio-lateral stability (in terms of cancelling time). Moreover, a medio-lateral instability associated with eye movement exploration before the promenade (in terms of body sway sensu stricto) was cancelled after the promenade. Finally, the overall medio-lateral stability (in terms of spectral power) increased after the promenade. Fourteen additional visitors were asked to sit in a dark room and adjust a luminous line to what they considered to be the earth-vertical axis. The promenade executed within the sculpted environment afforded by Serra’s monumental statuary works resulted in significantly improved performances on the subjective visual vertical test. We attribute these effects to the sculpted environment provided by the exhibition which may have acted as a kind of physiologic “training ground” thereby improving the visitors’ overall sense of visual perspective, equilibrium and gravity.